2006
DOI: 10.1121/1.2354071
|View full text |Cite
|
Sign up to set email alerts
|

The mean matters: Effects of statistically defined nonspeech spectral distributions on speech categorization

Abstract: Adjacent speech, and even nonspeech, contexts influence phonetic categorization. Four experiments investigated how preceding sequences of sine-wave tones influence phonetic categorization. This experimental paradigm provides a means of investigating the statistical regularities of acoustic events that influence online speech categorization and, reciprocally, reveals regularities of the sound environment tracked by auditory processing. The tones comprising the sequences were drawn from distributions sampling di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
136
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 56 publications
16
136
0
Order By: Relevance
“…Importantly, the effect of context was stronger if it was long (i.e., the full context) than if it was truncated. Listeners thus not only use various types of distal phonetic context information (i.e., spectral information (Holt, 2005); rhythmic information (Dilley & McAuley, 2008), speaking rate here) but the amount of this distal context modulates the strength of the effect (see also Holt, 2006, for effects of amount of spectral context information). In categorization tasks, listeners thus appear to be able to use all previous information, resulting in a cumulative effect of distal context.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the effect of context was stronger if it was long (i.e., the full context) than if it was truncated. Listeners thus not only use various types of distal phonetic context information (i.e., spectral information (Holt, 2005); rhythmic information (Dilley & McAuley, 2008), speaking rate here) but the amount of this distal context modulates the strength of the effect (see also Holt, 2006, for effects of amount of spectral context information). In categorization tasks, listeners thus appear to be able to use all previous information, resulting in a cumulative effect of distal context.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found that nonspeech contexts matched with speech contexts in the long-term average spectrum elicit similar normalization effects as speech contexts do (Huang & Holt, 2009;Holt et al, 1996;Holt, 2005Holt, , 2006aHolt, , 2006bLotto & Kluender, 1998;Lotto, Sullivan, & Holt, 2003;Watkins, 1991;Watkins & Makin, 1996) or even stronger effects sometimes (e.g., Laing et al, 2012). Because nonspeech contexts only contain auditory cues, it is argued that listeners rely on a general auditory mechanism in talker normalization, rather than a talker's acoustic-phonological space built from the context.…”
Section: Extrinsic Normalizationmentioning
confidence: 99%
“…2C). A series of follow-up experiments suggested that the auditory system maintains a running estimate of context and encodes incoming sound targets relative to that estimate (Holt, 2006). This running estimate lasts more than a second and is not disrupted by intervening neutral-frequency tones, noise, or silence.…”
Section: Phonetic Context Effectsmentioning
confidence: 99%